P074 The alarmin S100A9 hampers osteoclast differentiation from circulating precursors by reducing the expression of rank. (March 2019) - van den Bosch, MH; Di Ceglie, I; Blom, AB; Logie, C; Martens, JH; Roth, J; Vogl, T; Goodyear, CS; van der Kraan, PM; van Lent, PL
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: The alarmin S100A8/A9 is produced in high levels in inflamed synovium during arthritic diseases and has been implicated in sterile inflammation-induced bone resorption. We have previously shown that this alarmin increases the bone-resorptive capacity of mature osteoclasts. However, the effects on osteoclast differentiation remains elusive. Objectives: Here, we investigated the effects of S100A9 on osteoclast differentiation from CD14 + circulating precursors. Methods: CD14 + monocytes were isolated from buffy coats of healthy donors and differentiated towards osteoclasts with macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor kappa-B (RANK) ligand in the presence or absence of S100A9. Differentiation state of osteoclasts was determined by tartrate-resistant acid phosphatase (TRAP) staining and resorption capacity using hydroxyapatite-like-coated plates. RNA expression was analyzed with RNA sequencing and qPCR. RANK expression was assessed using FACS. Underlying epigenetic programming was studied using chromatin immunoprecipitation. Secretion of pro-/anti-inflammatory mediators was analyzed with Luminex analysis. Results: S100A9 stimulation during monocyte-to-osteoclast differentiation resulted in a strong decrease in the numbers of multinucleated osteoclasts, underlined by a decreased resorptive capacity. The thus differentiated cells showed a high production of pro-inflammatory factors, such as interleukin (IL)-1β, IL-6, IL-8, and tumor necrosis factor-α (TNFα) after 16 hour of stimulation. In contrast, at day 4, the cells showed a decreased expression of the osteoclast-promoting factor TNFα. Interestingly, S100A9 stimulation during the first 16 hour of culture was sufficient to reduce osteoclastogenesis. We observed that within this time frame, S100A9 inhibited the M-CSF-mediated induction of RANK, which associated with changes in various histone marks at the epigenetic level. This S100A9-induced reduction in RANK could be partially reversed by blocking TNFα, but not interleukin-1 (IL-1). Conclusions: Whereas S100A8/A9 was previously shown to stimulate the resorptive capacity of mature osteoclasts, we here show that early S100A9 stimulation impedes monocyte-to-osteoclast differentiation via reduction of RANK expression that is partially TNFα-mediated. This suggests that the timing of exposure to S100A8/A9 is an important determinant for monocyte-to-osteoclast differentiation. Disclosure of Interest: None declared.